Gendered Household Decision-Making in Lahore: Different Contextual Interpretations of qawwam in Qur’anic verse 4:34 - Rubab, Iram (Feminist theology, 2026)
Gendered household decision-making can be a substantive indicator of intrahousehold power relations; the role religion plays in shaping these is also critical. In Pakistan, the constitution, state legislation, and social relations are guided by shariah law. Drawing upon this context, this study questions the patriarchal interpretations of qur’anic verses that have reified gender inequality within Muslim families and societies. Our study is premised on the Islamic feminist perspective. The investigation was twofold in nature: first, through an extensive literature review of the term qawwam, explored in the context of Quranic verse 4:34, which is not only a controversial verse due to competing interpretations but also commonly understood to be establishing the higher status of men, under the three categories of classical, progressive, and Islamic feminist schools of thought. This became apparent during the research process. Second, the influence of the concept of qawwam on gendered household decision-making in Lahore was gauged through a self-administered survey conducted on 120 randomly selected respondents. The survey results were generated through descriptive statistical analysis. The findings of the study revealed that household decision-making was gendered with varied manifestations of male-dominated classical Islamic traditions. Seventy-five percent of the selected population believed qawwam to be in terms of male precedence in decision-making, and the data revealed that men decided 65% in matters of finances and 50% for external expenditures. By juxtaposing the varied theoretical interpretations with the predominantly singular idea of qawwam among the surveyed population, the study argues that it is imperative to revisit the contemporary popular interpretation; Muslim countries like Egypt have already made significant progress in such contexts.